DESCRIPTION OF BUKHARA IN THE WORK OF ABU BAKR NARSHAKHI (Scientific journal of the Fergana State University, 2023)
In this article, "History of Bukhara" written by Bukhara historian scholar Abu Bakr Muhammad ibn An Narshahi, who has a special place among the sources of information about the 8th-12th centuries of the Middle Ages and provides valuable information about the socio-economic, political and spiritual life of Movarunnahr and Khorasan. In his work, information related to the history of Bukhara is presented.